IMPROVING STUDENTS ACHIEVEMENT IN COMPREHENDING IMPERATIVE SENTENCES THROUGH TOTAL PHYSICAL RESPONSE - Nuryani, Tuti; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The purpose of this research is to describe how the total physical response improves the students achievement in comprehending imperative sentences. The method of this research is classroom action research in which concerned with improving the students comprehension of imperative sentences. The data of this research were collected by performance test and field note. The teacher instructed the students based on the procedure text, then the students showed the physical movement based on what the teacher instructed. The field note was used to observe everything happened in the classroom during the research. The improvement of the students achievement can be seen from the result in every cycle. After collecting and analyzing the data, it was found that total physical response could improve the students achievement in comprehending the imperative sentences. Based on the data, the mean score increased from the first cycle was 58.14; second cycle was 66,88 and the third cycle was 85.29. Shortly, the students had a better English teaching learning process through this activity. Keywords: improving, imperative sentences Abstrak: Tujuan dari penelitian ini adalah untuk mendeskripsikan bagaimana metode respon fisik total meningkatkan pencapaian siswa dalam memahami kalimat perintah. Metode dari penelitian ini adalah penelitian tindakan kelas yang terfokus pada peningkatan pemahaman siswa pada kalimat perintah. Data penelitian ini dikumpulkan melalui tes unjuk kerja dan catatan lapangan. Guru memberikan perintah kepada murid berdasarkan teks prosedur, kemudian siswa menunjukkan gerakan fisik berdasarkan perintah tersebut. Catatan lapangan digunakan untuk mengamati segala hal yang terjadi di ruang kelas selama penelitian berlangsung. Peningkatan pencapaian siswa dapat dilihat dari hasil disetiap siklus. Setelah mengumpulkan dan menganalisis data, ditemukan bahwa metode respon fisik total dapat meningkatkan pencapaian siswa dalam memahami kalimat perintah. Berdasarkan data yang dikumpulkan, nilai rata-rata pencapaian siswa meningkat dari siklus pertama yaitu 58.14; siklus kedua yaitu 66.88 dan siklus ketiga yaitu 85.29, sehingga bisa ditarik kesimpulan bahwa siswa mengalami proses pengajaran dan pembelajaran yang lebih baik melalui aktifitas belajar dengan metode respon fisik total. Kata kunci : meningkatkan, kalimat perintah